Algorithm for optimal denoising of Raman spectra. Issue 30 (19th July 2018) - Barton, Sinead J.; Ward, Tomas E.; Hennelly, Bryan M.
Abstract : The algorithm enhances Savitzky–Golay smoothing with maximum likelihood estimation, which outperforms traditional smoothing in terms of peak fidelity and SNR. Abstract : Raman spectroscopy has been demonstrated to have diagnostic potential in areas such as urine and cervical cytology, whereby different disease groups can be classified based on subtle differences in the cell or tissue spectra using various multi-variate statistical classification tools. However, Raman scattering is an inherently weak process, which often results in low signal to noise ratios, thus limiting the method's diagnostic capabilities under certain conditions. A common approach for reducing the experimental noise is Savitzky–Golay smoothing. While this method is effective in reducing the noise signal, it has the undesirable effect of smoothing the underlying Raman features, compromising their discriminative utility. Maximum likelihood estimation is a method for estimating the parameters of a statistical model given an available dataset and a priori knowledge of the model type. In this paper, we demonstrate how Savitzky–Golay smoothing may be enhanced with maximum likelihood estimation in order to prevent significant deviation from the 'true' Raman signal yet retain the robust smoothing properties of the Savitzky–Golay filter. The algorithm presented here is demonstrated to have a lower impact on Raman spectral features at known spectral peaks while providing superior denoising capabilities, when compared with established smoothing algorithms; artificially noised databases and experimental data are used to evaluate and compare the performance of the algorithms in terms of the signal to noise ratio. The proposed method is demonstrated to typically provide at least a 50% increase in the signal to noise ratio when compared to the raw data, and consistently out-performs two alternative smoothing filters.